Different Effects of Atorvastatin on Metabolic and Cardiovascular Risk Factors in Hypercholesterolemic Women with Normal Thyroid Function and Subclinical Hypothyroidism - Krysiak, R.; Gilowski, W.; Okopien, B. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Background: The presence of hypothyroidism seems to be associated with increased cardiovascular risk. No previous study compared circulating levels of plasma lipids and other cardiovascular risk factors in statin-treated patients with different thyroid function states.Methods: We studied 15 women with untreated subclinical hypothyroidism (group A), 16 women with treated hypothyroidism (group B) and 17 women with normal thyroid function (group C) who, because of coexistent hypercholesterolemia, were treated with atorvastatin. Plasma lipids, glucose homeostasis markers and plasma levels of cardiovascular risk factors were assessed before and after 12 weeks of therapy. 46 patients completed the study.Results: Baseline lipid levels were similar in all groups of patients. Plasma levels of high-sensitivity C-reactive protein (hsCRP), homocysteine and fibrinogen were higher in group A than in groups B and C. Although the effect on total and LDL cholesterol was observed in all treatment groups, it was less pronounced in patients with untreated hypothyroidism. Similarly, the effect of atorvastatin on hsCRP, homocysteine, fibrinogen and uric acid was stronger in groups B and C than in group A.Conclusions: Our results suggest that the effect of atorvastatin on plasma lipids and circulating levels of other cardiovascular risk factors partially depends on thyroid function.
Keywords: hypothyroidism; lipid profile; risk factors; statins